RELEVANT ALGORITHMS AND TECHNIQUES FOR BRAIN TUMOR SEGMENTATION USING MAGNETIC RESONACE IMAGING - Gurunathan, Pradeep; S, Preethi Saroj (International Journal of Psychosocial Rehabilitation, 2020)
Due to faster technological evolution, medical field too requires algorithms and techniques for carrying out diagnosis and treatment with better accuracy. Tumour segmentation plays a prominent role in medical image processes sing field. It aims to separate diseased tumour tissue from normal one with least error. Among various imaging modalities, Magnetic Resonance Imaging(MRI) is most predominantly used. MRI contains multiple noises, affecting the segmentation process. Hence the image has to be pre-processed to remove noises and improve data quality. This paper describes various segmentation techniques. Finally, evaluation metrics for analysing the segmentation techniques and some standard datasets are discussed.